2017
DOI: 10.1016/j.jacc.2016.10.067
|View full text |Cite
|
Sign up to set email alerts
|

SYNTAX Score and Long-Term Outcomes

Abstract: Among patients with diabetes and stable ischemic heart disease, higher SYNTAX scores predict higher rates of major cardiovascular events and were associated with more favorable outcomes of revascularization compared with medical therapy among patients suitable for CABG. (Bypass Angioplasty Revascularization Investigation in Type 2 Diabetes; NCT00006305).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
34
0
3

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 22 publications
2
34
0
3
Order By: Relevance
“…15,16 Use of the SYNTAX score assessment has been reported to help choose the strategy between CABG and PCI, and predict clinical outcomes, such as death, cardiac death, MI, and the composite of death/MI/stroke after PCI relative to CABG. [16][17][18] Although the J-CTO score is a scoring system to grade the difficulty of successful guidewire crossing of CTO lesions within 30 min, components of that score are mainly angiographic factors and previously treatment failure. In the present study, patients with high J-CTO score lesions were also correlated with clinical events, such as stroke and hospitalization for Abbreviations: CI, confidence interval; CTO, chronic total occlusion; PCI, percutaneous coronary intervention; TLR, target lesion revascularization.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Use of the SYNTAX score assessment has been reported to help choose the strategy between CABG and PCI, and predict clinical outcomes, such as death, cardiac death, MI, and the composite of death/MI/stroke after PCI relative to CABG. [16][17][18] Although the J-CTO score is a scoring system to grade the difficulty of successful guidewire crossing of CTO lesions within 30 min, components of that score are mainly angiographic factors and previously treatment failure. In the present study, patients with high J-CTO score lesions were also correlated with clinical events, such as stroke and hospitalization for Abbreviations: CI, confidence interval; CTO, chronic total occlusion; PCI, percutaneous coronary intervention; TLR, target lesion revascularization.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas, PCI among patients with a mid or high SYNTAX score, did not show significant reduction in MACE compared with medical therapy alone. Even more surprising in this stratum, patients randomized to PCI showed numerically higher rates of MACE compared to those assigned to medical therapy (35.6% vs. 26.5%, respectively, P=0.12) (11).…”
mentioning
confidence: 89%
“…In a current sub-analysis of Bypass Angioplasty Revascularization Investigation 2 Diabetes (BARI-2D) trial (10), Ikeno et al evaluated whether SYNTAX score predicted the effectiveness of coronary revascularization combined with medical therapy compared with medical therapy alone (11). The authors reported long-term outcome of 1550 patients with type 2 DM, stable CAD and no prior coronary revascularization.…”
mentioning
confidence: 99%
“…This was not shown in the PCI group. Importantly, there was even a strong trend to inferiority of the PCI group with numerically more endpoints reached after PCI compared to medical therapy alone (5).…”
mentioning
confidence: 99%
“…Indeed, there were higher levels of CAD in patients in the CABG group. This might have favored the outcome in the CABG group, since revascularization seems to be more successful in high risk patients with greater extent of CAD (5).…”
mentioning
confidence: 99%